Kurikulum Pendidikan Kewirausahaan Berbasis Akhlak Al-Karîmah Pesantren Darussyifa Al-Fitrah Sukabumi - Melani, Lani; Hafidhuddin, Didin; Syafri, Ulil Amri (Ta'dibuna: Jurnal Pendidikan Islam, 2018)
Pesantren Darussyifa Al-Fitrah Sukabumi already implementing a curriculum that combines akhlaq formation with entrepreneurship, especially for the female students, with the aim to produce graduates who are steadfast to the teachings of Islam and have an entrepreneurial spirit. This study tried to evaluate, analyze, and develop the implementation of the existing curriculum at the school in order to further strengthen akhlaq and entrepreneurial abilities of the female students. This study used a qualitative approach to the field, which is a combination of research conducted between objects of research conducted directly in the study area, combined with the research literature. In this case the researchers are trying to record the activities that occur in Pesantren Al-Fithrat Darussyifa Sukabumi, observing and collecting data from both direct and indirect sources. Furthermore, these results were analyzed based on the theories of existing experts. In addition, the researchers also tried to formulate the concept of entrepreneurship education curriculum based akhlaq al-karîma which is suitable to the female students at Pesantren Al-Fitrah Darussyifa Sukabumi. The results of this study showed that Pesantren Darussyifa Al-Fitrah Sukabumi already do the maximum to implement entrepreneurship education curriculum for the female students. In this case has been supported by exemplary models, coaching programmed, as well as the existing infrastructure. But researchers see there is still a weak point in terms of curriculum content, the process of implementation, and evaluation of the curriculum can be developed better. Keyword: education, entrepreneurship, exemplary model, female students